Implementation of Behavior Modification Techniques for Children with Low Social Skills (A Case Study at the Social Protection Service Unit for Children in Garut, West Java) - Subardhini, Meiti; Riyadi, Sabar; Sakroni, Sakroni (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This research focuses on the application of behavior modification techniques in various specific behaviors agreed upon, aiming to influence the levels of social skills. The research method employed is the Single Subject Design approach. The respondents of this study are children with low social skills receiving services at SATPEL PSA. Instruments used to measure baseline A1, treatment (B1), and baseline A2 are based on the results of behavior assessments, identifying 9 behaviors with 36 specific behaviors. The implementation of behavior modification techniques aims to reduce maladaptive behaviors in children, utilizing motivation techniques, positive reinforcement, modeling, counseling, and self-help groups. The research results indicate that two children, SS and MK, showed increased measurements in cognitive, behavioral, and emotional aspects during baseline and intervention. The highest results were recorded in the behavioral aspect, while the cognitive aspect showed a comparatively lower improvement.